Utilization of Information Technology for Communication and Learning for Students with Hearing Impairments - Wagino; Sujarwanto; Fairus Niratama (Universitas Pendidikan Ganesha, 2023)
Information technology (IT) is important to meet the needs of students with hearing disabilities in Indonesian special schools. The purpose of this study is to analyze the use and opinion of IT for communication and learning of students with hearing impairment in hearing impairment schools. IT in this study includes information devices such as mobile phones, smartphones, and tablets. This study used a stratified random sampling method to register the participants. Data were collected from 56 students with hearing loss using a self-administered questionnaire. The results found that most of these students knew about chat applications, for example, Whatsapp, Facebook, Instagram, and face-to-face conversation applications. Furthermore, most of these students contact people with hearing problems by sending messages via Facebook, Line apps, and face-to-face. The main reason why they use IT is for convenience and general conversation. A study of opinions on the use of IT by students with hearing impairment found that most of them agreed that IT devices contributed to their participation in various activities, including conversations with their relatives and friends on social networks.